1984
DOI: 10.1007/bf02534502
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of maternal food intake inhibits fatty acid activation in developing rat hearts

Abstract: We studied the effect of restricting the diet of pregnant and lactating rats on the beta-oxidation of fatty acids by the developing heart in suckling pups. Control pregnant rats were fed a stock diet ad libitum. For the experimental group, food was restricted to half of the control intake on the seventh day of pregnancy and continued through lactation. The pups on the restricted diet were significantly smaller than the controls. At postnatal days 5, 14 and 21, the beta-oxidation of [1-14C] palmitate by heart h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It has been shown that liver microsomal FACS activity varies with diet [. 13,14], In accordance with this, a shift from a high fat to a chow diet might have resulted in decreased FACS activity in weaned rats. There is also a possibility of other factors such as hormonal variations influencing the FACS activity after weaning.…”
Section: Discussionmentioning
confidence: 59%
“…It has been shown that liver microsomal FACS activity varies with diet [. 13,14], In accordance with this, a shift from a high fat to a chow diet might have resulted in decreased FACS activity in weaned rats. There is also a possibility of other factors such as hormonal variations influencing the FACS activity after weaning.…”
Section: Discussionmentioning
confidence: 59%
“…The observed reductions in the activities of the two cytochrome reductases in brain microsomes could reflect a generalised lowering of activity brought about by decreased availability of long chain fatty acyl CoA's, since these are known to be the true substrates of desaturases (21). Reports exist (22) to indicate that undernutrition does indeed lower the conversion of palmitate to palmitoyl CoA in certain tissues in young rats.…”
Section: Discussionmentioning
confidence: 99%